A STUDY ON ENVIRONMENTAL AWARENESS AMONG RESIDENTIAL AND NON RESIDENTIONAL SECONDARY SCHOOL STUDENTS - Suryakant, Dandinkar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The world today is facing multiple environmental crises due to the reckless and thoughtless exploitation of natural resources by humans. There is an urgent need to foster environmental awareness among individuals to ensure the conservation, protection, and sustainability of our environment. As a result, environmental education has been integrated into school curricula from an early stage. This study explores environmental awareness among secondary school students, comparing those in residential and non-residential settings, with a focus on gender and rural-urban differences. Environmental education plays a pivotal role in fostering sustainable behaviors and informed ecological practices. The study utilized a normative survey method and a self-designed environmental awareness questionnaire to assess the knowledge of 600 students across various demographic categories. The research findings reveal no significant difference in environmental awareness between residential and non-residential students. However, gender-based differences were observed, with female students consistently demonstrating higher environmental awareness than their male counterparts, particularly in residential settings. Additionally, the study identified a more pronounced gender gap in rural non-residential schools, where girls outperformed boys. These findings suggest that while residency status does not directly influence environmental awareness, gender and geographical context significantly impact students’ environmental attitudes. The study highlights the need for targeted educational interventions to engage male students, particularly in rural settings, and recommends curriculum modifications that address the specific needs of both genders. Educational policies should focus on fostering inclusive, community-based learning environments that encourage environmental literacy for all students, regardless of residency.